Monitoring Diseases in Water of Vannamei Shrimp (Litopenaeus Vannamei), Banyuwangi District - Andhika Putra Ramadhan; Ervina Wahyu Setyaningrum; Mega Yuniartik (Airlangga University, 2024)
Banyuwangi Regency has high potential for vannamei shrimp farming. Vannamei shrimp farming is susceptible to disease attack. Disease monitoring serves to determine the distribution of disease in vannamei shrimp ponds. The purpose of this study was to monitor disease in vannamei shrimp pond waters of Banyuwangi Regency. This research method uses descriptive method. Monitoring of water quality parameters insitu and exitu. Disease monitoring using Real-Time PCR Quant studio 5 to detect AHPND, WSSV, EHP, and IMNV. The analysis used was descriptive analysis. The results showed that the water quality in vannamei shrimp ponds in Banyuwangi Regency was an average temperature of 25.8â„ƒ, average salinity of 33.9 g.L-1 , average dissolved oxygen (DO) 7.15 mg.L-1 , average pH 8.15, average ammonia 0.257 mg.L-1 , average nitrite 0.04 mg.L-1 , average nitrate 4.9 mg.L-1 . As for the disease, there are three types, namely AHPND, EHP, and IMNV.